Novel Lys63-linked ubiquitination of IKKβ induces STAT3 signaling - Gallo, Leandro H (Cell Cycle, 2014)
NFκB signaling plays a significant role in human disease, including breast and ovarian carcinoma, insulin resistance, embryonic lethality and liver degeneration, rheumatoid arthritis, aging and Multiple Myeloma (MM). Inhibitor of κB (IκB) kinase β (IKKβ) regulates canonical Nuclear Factor κB (NFκB) signaling in response to inflammation and cellular stresses. NFκB activation requires Lys63-linked (K63-linked) ubiquitination of upstream proteins such as NEMO or TAK1, forming molecular complexes with membrane-bound receptors. We demonstrate that IKKβ itself undergoes K63-linked ubiquitination. Mutations in IKKβ at Lys171, identified in Multiple Myeloma and other cancers, lead to a dramatic increase in kinase activation and K63-linked ubiquitination. These mutations also result in persistent activation of STAT3 signaling. Liquid chromatography (LC)-high mass accuracy tandem mass spectrometry (MS/MS) analysis identified Lys147, Lys418, Lys555 and Lys703 as predominant ubiquitination sites in IKKβ. Specific inhibition of the UBC13-UEV1A complex responsible for K63-linked ubiquitination establishes Lys147 as the predominant site of K63-ubiquitin conjugation and responsible for STAT3 activation. Thus, IKKβ activation leads to ubiquitination within the kinase domain and assemblage of a K63-ubiquitin conjugated signaling platform. These results are discussed with respect to the importance of upregulated NFκB signaling known to occur frequently in MM and other cancers.